A comparison of transdiagnostic behavior therapy (TBT) and behavioral activation treatment for depression (BATD) in veterans with major depressive disorder. Issue 6 (22nd December 2021) - Gros, Daniel F.; Coyne, Alice E.
Abstract: Objectives: Although frequently discussed within the scope of transdiagnostic psychotherapy protocols, limited data are available on their efficacy in patients with a principal diagnosis of major depressive disorder. The present study attempted to address that gap in the literature through a randomized clinical trial comparing transdiagnostic behavior therapy (TBT) to behavioral activation treatment for depression (BATD). Methods: Forty veterans with principal major depressive disorder were randomized into either 12 sessions of individual TBT or BATD, with symptom measures collected at baseline and posttreatment. Process variables for treatment engagement and completion also were recorded. Results: Participants reported similar symptom improvements in depression, stress, anhedonia, and impairment across both treatments. Clinician‐rated treatment improvements favored TBT. Participants in TBT also attended more appointments, canceled or missed fewer appointments, and completed the protocol at a higher rate than participants that received BATD. Conclusions: The present findings support TBT as an efficacious treatment for principal major depressive disorder, with potentially superior coverage of comorbid anxiety symptomatology and improved treatment adherence and completion compared to BATD. Pending replication in larger samples, TBT and other similar transdiagnostic psychotherapies should be considered for implementation across the anxiety and depressive disorders to simplify dissemination efforts for evidence‐based psychotherapies and potentially improve coverage of comorbidity.